Volume Balance Method of Determining Infiltration in an Irrigation Border - Sharma, T.C. (Journal of Soil and Water Conservation, 2022)
The infiltration rate of water into soil is a time dependent function, beginning with relatively high value when the soil is first wetted and gradually diminishes to an almost constant rate known as basic intake rate. The knowledge of infiltration is of great importance to an irrigation engineer for planning and designing irrigation systems. The rate at which water can be applied and made available to the plants depends upon the infiltration capacity of the soil. The infiltration time function is a vital element in rational design of irrigation borders and furrows, since it effects the rate of advance of water furrows for given conditions of slope and size of irrigation streams.